Comparative Analysis to Evaluate FQ-EDCA in Wireless Ad-Hoc Networks - Hanal Abuzant (My University, 2014)
The QoS in wireless ad-hoc networks as defined by the standard IEEE802.11e (EDCA): functions so as to guarantee the high priority traffic (i.e. Multimedia and Real-time traffics). The QoS is managed in each station by differentiating the packets into categories depending on their priorities. These packets will access the channel with varying waiting times. However, EDCA cannot control traffic when there is a congestion to guarantee the QoS required by real-time and multimedia applications, specially when the problem of the hidden nodes exists. Thereby, the ill-behaved sources consume the majority of the available bandwidth. This leads some of the source nodes (i.e. Out of range nodes) to suffer from the lack of bandwidth and unfairness. So, without a proper control mechanism, this leads to degrading the QoS guarantees. To address this issue, we have proposed (FQ-EDCA): a Fairness Queuing model for EDCA. This paper aims to evaluate the scalability of FQ-EDCA and its network performance to have more end-to-end QoS guarantees.

البروتوكول القياسي الذي يشير الى جودة الخدمة المخصصة في الشبكات اللاسلكية هـو IEEE802.11e (EDCA). هذا البروتوكول يستخدم لضمان حركة مرور البيانات ذات الأولوية العالية (أي بيانات الوقت الحقيقي والوسائط المتعددة مثل الصوت والفيديو). علاوة علـى ذلك، تتم إدارة جودة الخدمة في كل محطة ارسال من تمييز الحزم المرسلـة الـى فئـات تبعـا لأولوياتها. بعد ذلك، هذه الحزم ستوزع اثناء ارسالها إلى قنوات مختلفة حسب وقت انتظارها ليتم ارسالها. ومع ذلك، لايمكن لEDCA مراقبة حركة البيانات عندما يكون هناك ازدحام وضغط على الشبكة اللاسلكية. مما سيؤثرعلى ضمان جودة الخدمة المطلوبة من قبل تطبيقات الوقت الحقيقي والوسائط المتعددة، وخاصة عندما تكون مشكلة المحطات المخفية (البعيدة) موجودة. وبالتالي، فإن سوء تصرف حجز الشبكة واستهلاك عرض النطاق الترددي المسموح به يؤدي إلى بعض المحطات سيعانون من عدم وجود عرض النطاق الترددي لارسال البيانـات. لذلك، من دون آلية الرقابة السليمة يؤدي إلى تدهور ضمانات جودة الخدمة. لذا، اقترحنـا(FQ-EDCA) . وهو نموذج جديد لتعديل قوائم الانتظار للبروتوكول المعلن بطريقة منصفة. يهدف هذا البحث إلى تقييم قابلية FQ-EDCA لحل المشاكل المعلنة و ضبط ضمان جودة الخدمة.
تقييم وتحليل (FQ-EDCA) في الشبكات اللاسلكية